Effectiveness of Using Video Tutorials in Physical Education Learning: Case Study at MA - Panjiantariksa, Yusuf (Champions: Education Journal of Sport, Health, and Recreation, 2024)
The purpose of this study was to evaluate how effective video tutorials are in teaching Physical Education at Madrasah Aliyah Darul Ulum Rejomulyo Barat, Magetan. Three main components were discussed in this study: student motivation, improvement of motor skills, and physical fitness. The results showed that video tutorials that had attractive and easy-to-understand visuals significantly increased student motivation. In addition, students improved their basic motor skills, such as running, jumping, and throwing; however, more complex techniques required additional guidance. Due to the lack of direct supervision during learning, fitness levels increased, but were not optimal. This study found that video tutorials can help physical education in the internet era, but they must be accompanied by direct supervision to achieve better results.